Bones at a crossroads Integrating Worked Bone Research with Archaeometry and Social Zooarchaeology - Wild, Markus; Thurber, Beverly A.; Rhodes, Stephen; Gates St-Pierre, Christian (Sidestone Press, 2021)
Bone tool studies are at a crossroads. A current path is to go beyond the concatenation of methods or concepts borrowed from other disciplines and aim instead at a truly integrated approach that is more in line with the objectives of interdisciplinary and transdisciplinary research. The papers in this volume follow this direction by adopting various forms of dialogue and integration between old and new methods and approaches, including technological analysis, usewear analysis, typology, zooarchaeology, stable isotope analysis, experimental archaeology or spatial analysis. They represent a mixture of methodological issues, case studies, and discussions of larger cultural and historical phenomena that span thousands of years and many parts of the World, from South Asia to the Near East and Europe, and from North to South America. The synergies deriving from these multi-perspective approaches lead to the repeated identification of diverse social aspects of past societies, including the identification of general social contexts of bone tool production and use, transmission of knowledge, the symbolic dimensions of artifacts, and intergroup relations as well as warfare and state formation processes. All these papers grew out of communications presented at the 13th meeting of the Worked Bone Research Group (WBRG) on October 7th-13th, 2019, at the Département d'anthropologie, Université de Montréal, Canada. The WBRG is an official working group of the International Council for Archaeozoology (ICAZ) dealing with the study of worked faunal remains from archaeological sites.